Komunikasi Organisasi di Tengah Kompleksitas Sistem Birokrasi - Kholid (Universitas Islam Darul Ulum Lamongan, 2025)
An organization is a structured system consisting of individuals who work together and collaboratively to achieve common goals and objectives. Work processes within an organization are based on authority, based on a clear division of labor, thus creating roles appropriate to their respective duties. In this context, the organization serves as a medium for carrying out managerial functions while simultaneously managing material and human resources in a coordinated manner, in accordance with the established formal division of tasks and authority. The concept of bureaucracy is based on legal legitimacy, not traditional authority or personal charisma. The characteristics of this system include a specific division of labor, structured with a clear hierarchy. However, the discourse on bureaucracy is always interesting to study, given its vital role in governance. On the one hand, bureaucracy is an institution that is indispensable to society, but on the other hand, it is often labeled as slow and cumbersome. Many people are reluctant to deal with bureaucracy because it is considered complicated and burdensome. This complex issue of Weberian organizations has given rise to the central role of organizational communication, which is needed as an effort to maintain the effective and efficient function and role of bureaucracy in society. The relationship between the discipline of communication and organizational structure, particularly within the Weberian model, lies in its focus on the interactions between individuals in achieving the institution's goals. Communication science focuses on the forms of communication implemented within organizations, the methods and techniques used, the media utilized, the message delivery process, and the obstacles that may arise in that communication process.